Alternative mRNA splice variants of the rat ClC-2 chloride channel gene are expressed in lung: genomic sequence and organization of ClC-2. - Chu, S (1997)
The ClC-2 epithelial cell chloride channel is a voltage-, tonicity- and pH-regulated member of the ClC super family. We have previously shown that rat lung ClC-2 (rClC-2) is down-regulated at birth, and molecular diversity is generated by alternative splicing [Murray et al. (1995) Am. J. Respir. Cell Mol. Biol. 12, 597-604; Murray et al. (1996) Am. J. Physiol. 271, L829-L837; Chu et al . (1996) Nucleic Acids Res. 24, 3453-3457]. To investigate other possible mRNA splice variations, we sequenced the entire rClC-2 gene and found that ClC-2Sa (formerly ClC-2S) results from the deletion of exon 20. The preceding intron 19 has an unusually high CT content and a rare AAG acceptor site. Because both features were also found in intron 13, we next tested the hypothesis that intron 13 would be involved in alternative splicing. As predicted, a second splice product, ClC-2Sb, was found by RT-PCR, but only in lung. When we compared the genomic maps of rClC-2 and human ClC-1 (hClC-1), striking similarities were found in each exon except for rClC-2 exon 20, which is absent in hClC-1. These observations suggest that ClC-1 and ClC-2 may have evolved by gene duplication, mutation and DNA rearrangement.